Pengaruh Audit Forensik, Audit Investigasi, Profesionalisme terhadap Pencegahan Kecurangan (Studi Empiris pada BPKP Provinsi Banten) - Roza Mulyadi; Muhammad Nawawi (FEB Universitas Sultan Ageng Tirtayasa, 2020)
The purpose of this study is to analyze the Forensic Audit Simulation, Investigative Audit, Professionalism, Fraud Prevention. This research was conducted on all auditors conducted on all internal and external auditors of BPKP Banten Province, where the number of internal auditors was 50 people and external auditors were 25 people. The sampling technique in this study used purposive sampling. The type of data used in research is quantitative data. The data source used in this study is primary data. Primary data obtained by distributing questionnaires to respondents. The results of this study indicate that the variable Forensic Audit, Investigative Audit procedures and Professionalism have proven effects on Fraud Prevention.